Employment risks and opportunities for an ageing workforce in the EU - Hartlapp, Miriam; Schmid, Günther (Berlin, 2008)
"The article provides a detailed analysis of the employment situation of older workers (55- 64 years) in the EU member states. Using European Labour Force Survey data we systematically discuss the variation in the employment of older workers along the dimensions of gender, sectoral distribution, type of employment, training and flexible work arrangements. We show that and where Germany has to do some catching up if it wants to create a favourable employment context for this age group. Highlighting country differences we draw the conclusions that this labour market challenge can be characterised to a large extent as a gender problem, that labour market policy for an ageing workforce must start much earlier than just with older people and that their employment situation can to a great extent be sought in the general economic parameters and especially in the degree of employment growth in the service sector."